Perspectives for high-performance permanent magnets: applications, coercivity, and new materials - Hirosawa, Satoshi; Nishino, Masamichi; Miyashita, Seiji (Advances in natural sciences. Nanoscience and nanotechnology, 2017)
High-performance permanent magnets are indispensable in the production of high-efficiency motors and generators and ultimately for sustaining the green earth. The central issue of modern permanent magnetism is to realize high coercivity near and above room temperature on marginally hard magnetic materials without relying upon the critical elements such as heavy rare earths by means of nanostructure engineering. Recent investigations based on advanced nanostructure analysis and large-scale first principles calculations have led to significant paradigm shifts in the understandings of coercivity mechanism in Nd-Fe-B permanent magnets, which includes the discovery of the ferromagnetism of the thin (2nm) intergranular phase surrounding the Nd sub(2) Fe sub(14) B grains, the occurrence of negative (in-plane) magnetocrystalline anisotropy of Nd ions and some Fe atoms at the interface which degrades coercivity, and visualization of the stochastic behaviors of magnetization in the magnetization reversal process at high temperatures. A major change may occur also in the motor topologies, which is currently overwhelmed by the magnetic flux weakening interior permanent magnet motor type, to other types with variable flux permanent magnet type in some applications to open up a niche for new permanent magnet materials.